HO-1 is located in liver mitochondria and modulates mitochondrial heme content and metabolism - Converso, Daniela Paola (2006)
This study investigated whether inducible HO-1 is targeted to mitochondria and its putative effects on oxidative metabolism in rat liver. Western blot and immune-electron microscopy in whole purified and fractionated organelles showed basal expression of HO-1 protein in both microsomes and mitochondria (inner membrane), accompanied by a parallel HO activity. Inducers of HO-1 increased HO-1 targeting to the inner mitochondrial membrane, which also contained biliverdin reductase, supporting that both enzymes are in the same compartmentalization. Induction of mitochondrial HO-1 was associated with a decrease of mitochondrial heme content and selective reduction of protein expression of cytochrome oxidase (COX) subunit I, which is coded by the mitochondrial genome and synthesized in the mitochondria depending on heme availability; these changes resulted in decreased COX spectrum and activity. Mitochondrial HO-1 induction was also associated with down-regulation of mitochondrial-targeted NO synthase expression and activity, resulting in a reduction of NO-dependent mitochondrial oxidant yield; inhibition of HO-1 activity reverted these effects. In conclusion, we demonstrated for the first time localization of HO-1 protein in mitochondria. It is surmised that mitochondrial HO-1 has important biological roles in regulating mitochondrial heme protein turnover and in protecting against conditions such as hypoxia, neurodegenerative diseases, or sepsis, in which substantially increased mitochondrial NO and oxidant production have been implicated.